Fluidized bed combustion in steam-rich atmospheres for high-nitrogen fuel: Nitrogen distribution in char and volatile and their contributions to NOx. (15th December 2016) - Zhang, Guangyi; Zhu, Chuanqiang; Ge, Yaxin; Liu, Xiaoxing; Xu, Guangwen
Highlights: Steam increased the concentrated nitrogen in char but decreased that in tar. Steam boosted generation of aliphatic hydrocarbons helpful for reducing NOx. Steam changed the peak release sequence of H2 to facilitate NOx reduction. S/F > 0.8 led to more NOx generated from char-N than from volatile-N. Abstract: This article is devoted to investigating the contributions of char-N and volatile-N to NOx formation from fluidized bed combustion of high-nitrogen fuel (distilled spirited lees (DSL)) in steam-rich atmospheres, to make clear the effect of steam on NOx reduction and the related mechanisms. The char and the volatile prepared by pyrolysis of the DSL were subjected to combustion tests in a fluidized bed to compare their NOx emission characteristics with that from combustion of the raw DSL, respectively. The results showed that with additional steam present in pyrolysis atmosphere, significantly more gas products were formed and bigger proportions of the total fuel nitrogen entered in the gas products. Additional steam also boosted generation of aliphatic hydrocarbons containing most of the nitrogen in the tar, which was helpful for reducing NOx. The presence of additional steam accelerated the release of the volatile and remarkably increased the yield of reducing pyrolysis gases and meanwhile changed the peak release sequence of H2, to facilitate NOx reduction. With increasing the mass ratio of steam to fuel (S/F), the total NOx from the DSL combustion at 900 °C in 25 vol.% O2 atmosphere and the conversion ratio of the char-N into NOx decreased but the contribution ratio of the char-N to the total NOx increased. When the S/F ratio exceeded 0.8 the char-N contributed more to the total NOx than the volatile-N did.